Remote monitoring of implantable cardioverter defibrillators: patient experiences and preferences for follow-up - Timmermans, Ivy; Zitron, Edgar (Pacing and clinical electrophysiology, 2019)
Background Patient satisfaction with remote patient monitoring (RPM) of implantable cardioverter defibrillators (ICDs) seems to be high, yet knowledge on long-term patient experiences is limited. The European REMOTE-CIED study explored patients' experiences with RPM, examined patient's preferences for ICD follow-up, and identified determinants of patient's preferences in the first 2 years postimplantation. Methods European heart failure patients (N = 300; median age = 66 years [interquartile range (IQR) = 59-73], and 22% female) with a first-time ICD received a Boston Scientific LATITUDE RPM system (Marlborough, MA, USA) and had scheduled in-clinic follow-ups once a year. Patients completed questionnaires at 1-2 weeks and also at 3, 6, 12, and 24 months postimplantation and clinical data were obtained from their medical records. Patient evaluation data were analyzed descriptively, and Student's t-tests/Man-Whitney U tests or Chi-square tests/Fisher's exact tests were performed to examine determinants of patient preferences. Results At 2 years postimplantation, the median patient satisfaction score with the RPM system was 9 out of 10 (IQR = 8-10), despite 53% of the patients experiencing issues (eg, failure to transmit data). Of the 221 patients who reported their follow-up preferences, 43% preferred RPM and 19% preferred in-clinic follow-up. Patients with a preference for RPM were more likely to be higher educated (P = 0.04), employed (P = 0.04), and equipped with a new LATITUDE model (P = 0.04), but less likely to suffer from chronic obstructive pulmonary disease (P = 0.009). Conclusion In general, patients were highly satisfied with RPM, but a subgroup preferred in-clinic follow-up. Therefore, physicians should include patients’ concerns and preferences in the decision-making process, to tailor device follow-up to individual patients’ needs and preferences.